Comprehensive assessment of the earth’s surface state disturbed by mining and ways to improve the situation: case study of Kryvyi Rih Iron-ore Basin, Ukraine - Bazaluk, Oleg; Petlovanyi, Mykhailo; Sai, Kateryna; Chebanov, Maksym; Lozynskyi, Vasyl (Frontiers in Environmental Science, 2024)
Introduction Complex mineral mining leads to critical earth’s surface disturbance and environmental pollution from industrial waste. This research aims to comprehensively study, assess and show the current scale of the earth’s surface disturbances in the largest mining region of Ukraine – the Kryvyi Rih. Iron-ore Basin and suggests ways to improve the situation based on backfill technologies for the earth’s surface rehabilitation and industrial waste utilization. Methods To identify the forms of surface disturbance, their parameters, and spatial location, satellite images of the region, government statistical data, and a geographic information system software suite were studied. An analysis of the effectiveness of existing reclamation measures for technogenic voids in the region was carried out, and a new concept of surface restoration was proposed using beneficiation tailings, which are difficult to utilize in the region. Results It has been determined that the contribution of the Kryvyi Rih Iron-ore Basin to waste generation is 92.08% of the total volume of waste accumulations in Dnipropetrovsk Oblast and 65.5% in Ukraine as a whole, amounting to 10.7 billion tons. It is determined that 65.25% of the total disturbed land area is industrial waste, 34.76% – quarry cavities and mine failure zones, occupying 49% of the Kryvyi Rih city area. An analysis of waste accumulation density in allotted areas shows that per 1 m2 of land area, on average, 183.5 tons of dump waste rocks and 73.5 tons of beneficiation tailings are placed. Disposal of beneficiation tailings is recognized as a priority, because their utilization is slower, occupy the largest area, creating a risk of dams breaching and intense dusting from tailings dams surface, threatening the environment and public health. For the first time in Ukraine, a concept for the earth’s surface rehabilitation for various industrial purposes has been developed based on paste backfill technologies. Discussion Paste backfill technology implementation is prioritized in the central and northern parts of the city, which can dispose of at least 65–70 million tons of waste in cavities and reclaim about 200 ha of land. The research results are valuable for the development of strategies or programs to overcome the technogenic-ecological crisis in the city. The rehabilitated earth’s surface can be usefully involved in various infrastructure projects for the development of the industrial and economic potential of an industrial city such as Kryvyi Rih.